The politics of familiarity: visual, liturgical and organisational conformity in the online church - Hutchings, Tim (Online - Heidelberg journal of religions on the internet, 2010)
“Online churches” are Internet-based Christian communities, pursuing worship, education, support, proselytisation and other religious goals through computer-mediated communication. This paper draws on three years of participant observation and 50 interviews to investigate reliance on the familiar in the aesthetics and sensory experience of online religion, a trend that previous researchers have noticed but not fully explained. I use two ethnographic studies to explore the range of motivations that can guide this common strategy and consider visual design, use of sound, avatar gestures, awareness of co-presence and the physical activity of the computer user. Key factors include the desire to “frame” participant expectations, “ground” online experience, demonstrate theological “authenticity” and encourage participatory leadership, and these achievements are used to validate experimentation in other areas. This strategy is not uncontested, however: “outsiders” are frequently deterred by styles that “insiders” consider “normal”, and both churches have begun to explore new forms of architecture, ritual and communication with no clear offline parallels. New blends of familiarity and innovation are emerging, indicating some of the future directions of online churchmanship. My two case studies, the Anglican Cathedral of Second Life and LifeChurch.tv Church Online, reflect two key trends among online churches: the proliferation of small-scale independent congregations and the increasing involvement of wealthy institutions. The empirical and theoretical dimensions of this paper are innovative and timely, drawing attention to the professionalization and domestication of online religion and the rise of the “online campus”, key developments that deserve considerable scholarly attention.